2002
DOI: 10.1007/s00213-002-1154-7
|View full text |Cite
|
Sign up to set email alerts
|

The 5-choice serial reaction time task: behavioural pharmacology and functional neurochemistry

Abstract: The monoaminergic and cholinergic systems appear to play separable roles in different aspects of performance controlled by the 5CSRTT, in neural systems centred on the prefrontal cortex, cingulate cortex and striatum. These conclusions are considered in the methodological and theoretical context of other psychopharmacological studies of attention in animals and humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

54
1,256
8
12

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,184 publications
(1,330 citation statements)
references
References 80 publications
(145 reference statements)
54
1,256
8
12
Order By: Relevance
“…Striatal ACh increase associated with cocaine acquisition Crespo et al, 2006;Mark et al, 1999) Striatal ACh alters cocaine-induced locomotor sensitization Hikida et al, 2001Hikida et al, , 2003 mACh receptors decrease after chronic cocaine (Lipton et al, 1995;Macedo et al, 2004;Wilson et al, 1994;Zeigler et al, 1991) Amygdala mAChR may facilitate acquisition of associative learning underlying context-dependent sensitization Itzhak and Martin, 2000) Explicit memory Hippocampus ACh involved in the encoding of new information (Hasselmo and Fehlau, 2001;Hasselmo et al, 2002) Hippocampal ACh increases following cocaine use (Imperato et al, 1993a(Imperato et al, , b, 1996Smith et al, 2004a, b) Conditioned learning VTA VTA ACh involved in conditioned learning (Bechara and van der Kooy, 1989;Museo and Wise, 1994;Olmstead and Franklin, 1993) M 5 -deficient rats decrease cocaine-induced CPP (Fink-Jensen et al, 2003) Striatum Striatal ACh involved in conditioned learning (Legault et al, 2006) NAc ACh inhibits cocaine-induced CPP (Hikida et al, 2001 ACh antagonist blocks induction of locomotor sensitization to cocaine-induced CPP (Itzhak and Martin, 2000) Amygdala Amygdalar ACh facilitates conditioned learning (McIntyre et al, 1998;Power et al, 2003) Amygdalar ACh alters cocaine-induced conditioned learning (See et al, 2003;Zeigler et al, 1991) Attention PFC Elevated ACh may focus attentional resources toward salient stimuli (Baxter and Chiba, 1999;Robbins, 2002;Sarter et al, 2003) Cocaine-addicted subjects show impaired attention (Horner et al, 1996;Jovanovski et al, 2005) Set shifting PFC ACh involved in set shifting (Ragozzino and Choi...…”
Section: Overview Of Animal Models Of Addictionmentioning
confidence: 99%
See 1 more Smart Citation
“…Striatal ACh increase associated with cocaine acquisition Crespo et al, 2006;Mark et al, 1999) Striatal ACh alters cocaine-induced locomotor sensitization Hikida et al, 2001Hikida et al, , 2003 mACh receptors decrease after chronic cocaine (Lipton et al, 1995;Macedo et al, 2004;Wilson et al, 1994;Zeigler et al, 1991) Amygdala mAChR may facilitate acquisition of associative learning underlying context-dependent sensitization Itzhak and Martin, 2000) Explicit memory Hippocampus ACh involved in the encoding of new information (Hasselmo and Fehlau, 2001;Hasselmo et al, 2002) Hippocampal ACh increases following cocaine use (Imperato et al, 1993a(Imperato et al, , b, 1996Smith et al, 2004a, b) Conditioned learning VTA VTA ACh involved in conditioned learning (Bechara and van der Kooy, 1989;Museo and Wise, 1994;Olmstead and Franklin, 1993) M 5 -deficient rats decrease cocaine-induced CPP (Fink-Jensen et al, 2003) Striatum Striatal ACh involved in conditioned learning (Legault et al, 2006) NAc ACh inhibits cocaine-induced CPP (Hikida et al, 2001 ACh antagonist blocks induction of locomotor sensitization to cocaine-induced CPP (Itzhak and Martin, 2000) Amygdala Amygdalar ACh facilitates conditioned learning (McIntyre et al, 1998;Power et al, 2003) Amygdalar ACh alters cocaine-induced conditioned learning (See et al, 2003;Zeigler et al, 1991) Attention PFC Elevated ACh may focus attentional resources toward salient stimuli (Baxter and Chiba, 1999;Robbins, 2002;Sarter et al, 2003) Cocaine-addicted subjects show impaired attention (Horner et al, 1996;Jovanovski et al, 2005) Set shifting PFC ACh involved in set shifting (Ragozzino and Choi...…”
Section: Overview Of Animal Models Of Addictionmentioning
confidence: 99%
“…Attention refers to the different capacities or processes that relate to how an organism becomes receptive to stimuli and how it begins to process incoming or attended-to (internal or external) excitation (Parasuraman, 1998). ACh is strongly linked to these attentional processes (Baxter and Chiba, 1999;Robbins, 2002;Sarter et al, 2003). ACh efflux, for example, is increased into the medial frontal cortex during a five-choice serial reaction time task (5-CSRTT)Fa measure of visual attention.…”
Section: Acetylcholine and Prefrontal Cortical Cognitionmentioning
confidence: 99%
“…The relationship between 5-HT function and behavioral inhibition has been studied using a number of different animal models combined with manipulations of the 5-HT system (Soubrié, 1986;Robbins, 2002;Chudasama and Robbins, 2004;Winstanley et al, 2006). Depletion of forebrain 5-HT induces impulsive responding in rats when assessed using go/no-go or DRL paradigms (Fletcher, 1995;Harrison et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Impulsivity, as measured by the 5-choice serial reaction time task (5CSRTT), has also been shown to be sensitive to 5-HT manipulations. The 5CSRTT assesses aspects of impulse control as well as attentional performance, speed of responding and motivation (Carli et al, 1983;Robbins, 2002). Harrison et al (1997a) showed that global 5-HT depletion increases premature responding on the 5CSRTT with concurrent decreases in omissions and latency to make a correct response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation